Electroweak phase transitions in multi-Higgs models: the case of Trinification-inspired THDSM - Vieu, Thibault (2019)
The rich vacuum structure of multi-Higgs extensions of the Standard Model (SM) may have interesting cosmological implications for the electroweak phase transition (EWPT). As an important example of such class of models, we consider a particularly simple low- energy SM-like limit of a recently proposed Grand-Unified Trinification model with the scalar sector composed of two Higgs doublets and a complex singlet and with a global U(1) family symmetry. The fermion sector of this model is extended with a family of vector-like quarks which enhances CP violation. With the current study, we aim at exploring the generic vacuum structure and uncovering the features of the EWPT in this model relevant for cosmology. We show the existence of different phase transition patterns providing strong departure from thermal equilibrium. Most of these observations are not specific to the considered model and may generically be expected in other multi-Higgs extensions of the SM.